Non-G-10 Countries and the Basle Capital Rules : How Tough a Challenge is it to Join the Basle Club? - Dziobek, Claudia; Frecaut, Olivier; Nieto, Maria (Washington, D.C. : International Monetary Fund, 1995)
The 1988 Basle Capital Accord has introduced the norm of a risk-based capital ratio of 8 percent. It was negotiated among the G-10 countries to strengthen their international banks' capital base while simultaneously levelling the playing field for competition. Since 1988, a large number of non-G-10 countries, although not members of the 'Basle Club,' have introduced similar risk-based capital ratios, hoping to achieve similar effects in terms of enhanced safety and competition in their banking markets. This paper explains why the endeavor failed in most cases and discusses what the required conditions would be for effective implementation of the Basle rules beyond the G-10 countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet